Social capital, institutional structures, and democratic performance: A comparative study of German local governments - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
A great deal of attention has been given recently to the political culture approach in the form of Putnam's argument regarding the importance of social capital in shaping performance in both the political and economic systems. One implication that can be drawn from his study of Italian regional governments is that in the absence of large stocks of social capital, governmental institutions cannot be constructed that would afford superior democratic performance. While entertaining the hypothesis that social capital contributes to government performance, this paper also argues that institutional differences in government forms doplayan important role in shaping the levels of citizen satisfaction with their governments. In particular, it is argued that by minimizing the number of potential veto players within the institutional structure of the government decision making system, performance can be heightened. Drawing mainly on data from two surveys (of elites and citizens) in a large number of German communities conducted during 1995, an assessment of the cultural and institutional hypotheses is carried out. The results suggest that social capital (at least that manifested within local elite political culture) does contribute to better performance. In addition, regardless of the level of social capital that marks a community, governmental performance is enhanced through institutional structures that lower or minimize the number of veto players. – – Dem Politischen-Kultur-Ansatz wird derzeit durch Putnams Argument der Bedeutung des Sozialkapita1s bei der Gestaltung der Performanz politischer und ökonomischer Systeme große Aufmerksamkeit gewidmet. Als eine Implikation aus seiner Untersuchung der Regionalregierungen in Italien kann angenommen werden, daß bei nicht vorhandenem Sozialkapital keine staatlichen Institutionen geschaffen werden können, die eine bessere demokratische Performanz bieten könnten. Der Hypothese, daß Sozialkapital zur Regierungsperformanz beiträgt, folgend, wird in dem vorliegenden Papier argumentiert, daß institutionelle Unterschiede in den Regierungsformen doch eine wichtige Rolle bei der Bestimmung des Grades der Zufriedenheit der Bürger mit ihren Regierungen spielen. Speziell wird nachgewiesen, daß durch eine Minimierung der Anzahl potentieller Vetoakteure innerhalb der institutionellen Struktur des Entscheidungssystems der Regierung die Performanz erhöht werden kann. Unter Nutzung der Daten aus zwei Umfragen (Eliten und Bürger), die 1995 in einer großen Anzahl deutscher Gemeinden durchgeführt wurden, wird eine Einschätzung der kulturellen und institutionellen Hypothesen vorgenommen. Die Ergebnisse legen nahe, daß das Sozialkapital (zumindest jenes, welches sich in der politischen Kultur der lokalen Eliten manifestiert hat) wirklich zu einer besseren Performanz beiträgt. Darüber hinaus wird die Regierungsperformanz - ungeachtet des Niveaus des Sozialkapitals, das die spezielle Gemeinde auszeichnet - durch institutionelle Strukturen verbessert, die die Zahl der Vetoakteure verringern bzw. minimieren.
Keywords: 300